Pengembangan Media Pembelajaran Elektronik Berbasis Masalah pada Mata Pelajaran Komputer dan Jaringan Dasar - Eko Ady Saputra; Wakhinuddin Wakhinuddin; Fahmi Rizal (Jurnal Pendidikan Teknologi Kejuruan, 2019)
This study aims to obtain valid, practical, and effective problem-based electronic learning media on the computer and basic network subjects. Problem-based electronic learning media is designed to be able to improve student understanding and activities so as to improve learning outcomes. This research uses Research and Development (R and D) research method with 4-D development procedures (define, design, develop, and disseminate). Data analysis techniques used descriptive analysis techniques to describe the validity, practicality, and effectiveness of problem-based electronic learning media. The results obtained from this development research: (1) the validity of problem-based electronic learning media is declared validly on media aspects and material aspects (2) the practicality of problem-based electronic learning media based on teacher and student responses is declared very practically (3) the effectiveness of learning media Problem-based electronics are declared effective in improving learning outcomes and learning motivation. Based on the findings of this study concluded that the problem-based electronic learning media is declared validly, practical and effective to be used as teaching materials in the Computer and Basic Network subjects